2016
DOI: 10.1002/elps.201600126
|View full text |Cite
|
Sign up to set email alerts
|

Separation of high‐purity syringol and acetosyringone from rice straw‐derived bio‐oil by combining the basification‐acidification process and column chromatography

Abstract: Numerous technologies have been used to reclaim valuable chemicals from bio-oil. In this study, a combination of the basification-acidification process and column chromatography was employed for the separation of high-purity syringol and acetosyringone from rice straw-derived bio-oil. The optimal conditions for the basification-acidification process and the possible precipitation mechanism of the basification were explored. The results showed the following as the optimal conditions for the basification process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…However, the results of the studies by Zhou et al 52 and Li et al 54 cannot exclude the formation of a cross-linked structure, like lignin-O-Ca-O-ϕlignin. Instead, the FT-IR spectra of lignin-calcium hydroxide recorded by Zhou et al 52 and Li et al 54 and the FT-IR spectra for various pure (methoxy)phenols precipitated with calcium hydroxide recorded by Schlosberg and Scouten 56 and Hao et al 74 seem to support the hypothesis that two lignin-phenolic moieties react with calcium hydroxide and thus induce cross-linking.…”
Section: Pyrolysis Liquid Compositionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, the results of the studies by Zhou et al 52 and Li et al 54 cannot exclude the formation of a cross-linked structure, like lignin-O-Ca-O-ϕlignin. Instead, the FT-IR spectra of lignin-calcium hydroxide recorded by Zhou et al 52 and Li et al 54 and the FT-IR spectra for various pure (methoxy)phenols precipitated with calcium hydroxide recorded by Schlosberg and Scouten 56 and Hao et al 74 seem to support the hypothesis that two lignin-phenolic moieties react with calcium hydroxide and thus induce cross-linking.…”
Section: Pyrolysis Liquid Compositionmentioning
confidence: 95%
“…52,56 This peak was, however, not observed in the FT-IR spectra for lignin to which calcium hydroxide was added. 52,54 The addition of calcium hydroxide to pure methoxyphenols (guaiacol, syringol, 4-ethylguaiacol, and acetosyringone), phenol, and 4-ethylphenol by Hao et al 74 led to a precipitate in case of the methoxyphenols, but not for phenol and 4-ethylphenol. Those precipitates also lacked a characteristic peak for OH at ν = 3640 cm −1 , which would be apparent if half salts would have been formed.…”
Section: Pyrolysis Liquid Compositionmentioning
confidence: 99%
“…They are major constituents of wood smoke condensate and identified as having a woody/herby flavor and smoky odor (Maga 1987). Syringol is also been isolated from rice straw derived bio-oil (Hao, Chen et al 2016). Apart from being a constituent of wood smoke, syringol is shown to exhibit different bio-functions.…”
Section: Discussionmentioning
confidence: 99%
“…The eluents used in bio-oil separation are hexane, toluene, benzene, pentane, ethyl acetate, and methanol [72][73][74]. However, Hao et al [75] reported that the valuable chemical compound like syringol and acetosyringone can be effectively separated from column chromatography.…”
Section: Column Chromatographymentioning
confidence: 99%